Forests and Food (2019)
As population estimates for 2050 reach over 9 billion, issues of food security and nutrition have been dominating academic and policy debates. A total of 805 million people are undernourished worldwide and malnutrition affects nearly every country on the planet. Despite impressive productivity increases, there is growing evidence that conventional agricultural strategies fall short of eliminating global hunger, as well as having long-term ecological consequences. Forests can play an important role in complementing agricultural production to address the Sustainable Development Goals on zero hunger. Forests and trees can be managed to provide better and more nutritionally-balanced diets, greater control over food inputs–particularly during lean seasons and periods of vulnerability (especially for marginalised groups)–and deliver ecosystem services for crop production. However forests are undergoing a rapid process of degradation, a complex process that governments are struggling to reverse. Forests have huge potential to reduce global hunger and malnutrition. Forests and Food provides the evidence and insights necessary for harnessing that power. This timely volume is essential reading for researchers, students, NGOs and governments around the globe.